Analytical Investigation of 8-Channel Optical Wavelength Division Multiplexing Communication System - Mohammed Hussian Ali (Engineering and Technology Journal, 2010)
In this paper, the theoretical 8-channel Dense Wave Division Multiplexing(DWDM) telecommunication system is demonstrated. Laser Diode (LD) sourcewas used for each channel, with external modulator, therefore making the systemwork at high bit rate. The analytical part was done using a software simulator. Allthe proposed system components were simulated using Optisystem software offeredby Optiwave for testing a DWDM communication system. The 8-channel DWDMspectrum, attenuation, dispersion, and receiver performance was determined.